2011
DOI: 10.1038/ncomms1520
|View full text |Cite
|
Sign up to set email alerts
|

The NMR structure of stomagen reveals the basis of stomatal density regulation by plant peptide hormones

Abstract: stomatal development in plants is regulated by defensin-like secretory epidermal patterning factor (EPF) peptide hormones. only one of these, stomagen, is a positive regulator, whereas EPF1, EPF2, and possibly others are negative regulators. Here we explore the structure-function relationships of EPFs, by integrating nmR and semi-in vitro stomagen experiments. We show that stomagen is composed of a loop and a scaffold containing three disulphide bonds. A mutant composed of the stomagen loop and the EPF2 scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 37 publications
9
117
0
Order By: Relevance
“…The nuclear magnetic resonance (NMR) structure of the EPF family peptide EPFL9/Stomagen revealed a conserved peptide backbone composed of an antiparallel b sheet supported by three disulfide bonds, which is intercepted by a less conserved loop domain (Ohki et al 2011). Domain-swap experiments between EPFL9/ Stomagen and EPF2, which are positive and negative regulators of stomatal development, respectively, revealed that the divergent loop domain is likely to determine the functional specificity of each EPF peptide (Ohki et al 2011).…”
Section: Molecular Characteristics Of Cle and Epf Family Peptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…The nuclear magnetic resonance (NMR) structure of the EPF family peptide EPFL9/Stomagen revealed a conserved peptide backbone composed of an antiparallel b sheet supported by three disulfide bonds, which is intercepted by a less conserved loop domain (Ohki et al 2011). Domain-swap experiments between EPFL9/ Stomagen and EPF2, which are positive and negative regulators of stomatal development, respectively, revealed that the divergent loop domain is likely to determine the functional specificity of each EPF peptide (Ohki et al 2011).…”
Section: Molecular Characteristics Of Cle and Epf Family Peptidesmentioning
confidence: 99%
“…Domain-swap experiments between EPFL9/ Stomagen and EPF2, which are positive and negative regulators of stomatal development, respectively, revealed that the divergent loop domain is likely to determine the functional specificity of each EPF peptide (Ohki et al 2011). It would be enlightening to investigate further the relationship between structure and biological function by analyzing the loop region and its binding affinity to the receptor among EPF family members known to have different and redundant biological functions.…”
Section: Molecular Characteristics Of Cle and Epf Family Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context as well, signaling peptides have a significant impact on development [44,[72][73][74]. Multiple cysteine-rich signaling peptides that belong to the EPF family, in particular EPF1, EPF2, EPF-LIKE6/CHALLAH (EPFL6/CHAL) and EPFL9/ STOMAGEN, are associated with the regulation of stomatal density and positioning [18,19,44,72,[75][76][77][78]. Overexpression of EPF1 and EPF2 reduces stomatal density.…”
Section: Epidermal Patterning Factor/ Efp-like (Epf/epfl)mentioning
confidence: 99%